Akibat Hukum Pembatalan Perkawinan Menurut Undang-Undang Nomor 1 Tahun 1974 - Risma A’limathus Zuriah; Dewi Murniati (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
This study examines the legal consequences of annulment of marriage according to Law Number 1 of 1974. The main focus is on Law (UU) No. 1 of 1974 concerning the legal consequences of annulment of marriage. Using qualitative methods, this study analyzes the legal consequences of annulment of marriage contained in Law No. 1 of 1974. Then Law No. 1 of 1974 is used as a legal basis that explains marriage and annulment of marriage. This study concludes that annulment of marriage has very large legal consequences for the husband and wife, one of the causes of which is the invalidity of the marriage due to the failure to fulfill the requirements set by the court.